Antibacterial Activity of Ethanol Extract and Fraction of Daemonorops draco (Willd.) Blume. Fruit - Samaniyah, Siti; Masfria; Sitorus, Panal (International Journal of Science, Technology & Management, 2022)
Daemonorops draco is a type of draco (Willd.) Blume fruit is well-known as an antiseptic, increases blood circulation, anti-microbial, anti-viral, anti-tumor, wound medicine, diarrhea, fractures, gonorrhea, mild burns, and other traditional medicines. Daemonorops draco is a type of draco (Willd.) Blume belongs to the Arecaceae family and contains alkaloids, flavonoids, tannins, saponins, steroids / triterpenoids, and glycosides, among other chemical components. Chemical compounds such as flavonoid compounds, saponins, and tannins have antibacterial and antiviral properties. Simplicia features, phytochemical screening, and antibacterial activity testing of ethanol extract and fruit fractions of Daemonorops draco (Willd.) Blume are all part of this study. Organoleptic, macroscopic, and microscopic tests were performed on the simplicia, as well as water content measurement on ethanol extracts. Maceration with ethanol as the solvent was followed by fractionation with n-hexane and ethylacetate as solvents. The phytochemical screening was done on Daemonorops draco (Willd.) Blume simplicia powder, extract, and fruit fraction. The antibacterial activity of each fraction was determined by examining the zone of inhibition against different test species, including Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), and Salmonella typhi (ATCC 25923). (ATCC 6539). The water content of the simplicia was 4.65 percent, and the ethanol extract was 5.98 percent, according to the results of the characterisation. Alkaloids, flavonoids, glycosides, saponins, tannins, and steroids/triterpenoids were found in the phytochemical screening test of the ethanol extract. At a concentration of 25 mg/ml, Staphylococcus aureus had the highest antibacterial activity with an effective inhibitory diameter of 15.3 mm, Escherichia coli had the highest antibacterial activity with an effective inhibitory diameter of 14.2 mm, and Salmonella typhi had the highest antibacterial activity with an effective inhibitory diameter of 14.5 mm.